Decoding Diversity: Indonesian Student’ Reception of Religious and Multicultural Themes in ‘Mentega Terbang’ Using Stuart Hall’s Encoding/Decoding Framework - Annisa, Firly; Nurnisya, Frizki Yulianti; Sofian, Muhammad Raqib Bin Mohd; Pradipta, Elita Putri; Soliman, Eman M. (CHANNEL: Jurnal Komunikasi, 2025)
This research explores the reception of the Malaysian film "Mentega Terbang" among students at Universitas Muhammadiyah Yogyakarta (UMY). The film has sparked controversy in Malaysia due to its portrayal of elements perceived to be insensitive to Islam, the predominant religion in the country. Using Stuart Hall's encoding/decoding model as a research framework, this study investigates how Indonesian students interpret and engage with the film's themes and controversies. The methodology employed in this research involves qualitative analysis of audience reception. Data was gathered through focus group discussions and individual interviews conducted with UMY students. The findings reveal diverse interpretations among Indonesian students regarding the portrayal of questioning religion during childhood as a common and acceptable theme. Many students argue that such themes should not necessarily provoke controversy but rather reflect everyday experiences and discussions. Overall, this study contributes to understanding how media messages, particularly those involving sensitive cultural and religious themes, are received and interpreted by different audience groups. It underscores the variability in audience perceptions and highlights the importance of context and cultural background in shaping interpretations of media content.